Soil properties, tomato (Solanum lycopersicum) yield and monetary returns under different nutrient management practices - NANDHINI, D UDHAYA; VENKATESAN, S; K SENTHILRAJA; SOMASUNDARAM, E (The Indian Journal of Agricultural Sciences, 2024)
The experiment was conducted during 2019 and 2020 at research farm of Tamil Nadu Agricultural University, Coimbatore, Tamil Nadu to study the effect of different manures proportion along with reduced fertilizers rate application on performance of tomato (Solanum lycopersicum L.) yield, produce quality and soil fertility indicators. Experiment was laid out in randomized block design (RBD) comprised of 6 treatments, viz. T1, 100% organic; T2, 75% organic + 3% Panchagavya spray + azophos @3 kg; T3, 100% inorganic recommended dose of fertilizer (RDF) alone; T4, State recommendation; T5, 50% organic + 50% inorganic; and T6, 75% organic + 25% inorganic. The results of two years mean showed that the soil quality indicators like SOC (8.12 g/kg), mineral N (266 kg/ha), available P (22.1 kg/ha), exchangeable K (482 kg/ha), microbial biomass carbon (256 mg/kg), dehydrogenase (35.8 μg TPF/g/ day), alkaline phosphatase (475 μg PNP/g/soil/h), bacteria (38.4 CFU × 106/g soil), fungi (15.0 CFU × 103/g soil) and actinobacteria population (10.3 CFU × 105/g soil) were better under 75% organic + 25% organic. Tomato yield was at par with 100% organic. On the basis of the above results, the tomato yield can be enhanced by about 99% and 150% in terms of production and monetary efficiency by the adoption of integrated nutrition management (INM) of organic (75%) and inorganic fertilizers (25%). Thus, the results suggest that the 75% organic + 25% inorganic could be adopted to get maximum benefits in terms of yield, fruit quality, soil fertility and fertilizer savings.